1991
DOI: 10.1115/1.2899676
|View full text |Cite
|
Sign up to set email alerts
|

Ductile-Regime Grinding: A New Technology for Machining Brittle Materials

Abstract: Because of recent advances in precision engineering that allow controlled grinding infeed rates as small as several nanometers per grinding wheel revolution, it is possible to grind brittle materials so that the predominant material-removal mechanism is plastic-flow and not fracture. This process is known as ductile-regime grinding. When brittle materials are ground through a process of plastic deformation, surface finishes similar to those achieved in polishing or lapping are produced. Unlike polishing or lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
421
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 889 publications
(426 citation statements)
references
References 9 publications
2
421
0
3
Order By: Relevance
“…Equations have also been reported to determine this critical UCT. Given by Biffano et al [39], a model was derived based on Griffith fracture criterion. The critical UCT d c is expressed by…”
Section: Critical Undeformed Chip Thicknessmentioning
confidence: 99%
“…Equations have also been reported to determine this critical UCT. Given by Biffano et al [39], a model was derived based on Griffith fracture criterion. The critical UCT d c is expressed by…”
Section: Critical Undeformed Chip Thicknessmentioning
confidence: 99%
“…Conversely, the ductile regime machining method is emerging as a good way to solve the fracture problem, in which work materials are removed in the form of sheared machining chips and leave a crack-free machined surface. Based on the Griffith energy criterion, Bifano et al [7] proposed that the critical grinding depth for ductile mode grinding of brittle materials was associated with material intrinsic properties. It indicated that the energy required for plastically deformation is less than that for fracture especially at small material removal scale.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that during abrasive machining the removal of a brittle material could be transited from brittle to ductile mode if the cutting depth of an abrasive grit was kept below a threshold value [25]. Under such conditions, plastic flow would become A c c e p t e d M a n u s c r i p t 28 predominant in the material removal and good surface integrity could be achieved in the grinding of brittle materials [6,[10][11][12].…”
Section: Grinding Characteristicsmentioning
confidence: 99%
“…15(a), the surface roughness of glass substrate exhibits a good dependency to h m , except for the two conditions marked in the red circle, where the SEM surface characterization showed severe fracture occurred on glass. The critical grit depths of cut for glass, SnO 2 and a-Si were estimated using the Bifano model [25], which are approximately 70 nm [26,27], 30 nm [28,29] and 140 nm [30,31], respectively. As the values of h m used in our grinding experiment were smaller than the critical depth for ductile-to-brittle transition in glass, the removal of glass substrate was expected in the ductile region.…”
Section: Page 29 Of 43mentioning
confidence: 99%